'We are the barriers': Danish general practitioners' interpretations of why the existential and spiritual dimensions are neglected in patient care. (19th October 2017) - Assing Hvidt, Elisabeth; Søndergaard, Jens; Hansen, Dorte; Gulbrandsen, Pål; Ammentorp, Jette; Timmermann, Connie; Hvidt, Niels
Abstract : Although it is broadly recognized that health problems often involve existential and spiritual dimensions, recent research shows that these aspects of illness are rarely attended to by health professionals. Studies explain this in terms of barriers to communication, but health professionals' firsthand experiences and interpretations have so far been largely unexplored. Drawing on the theoretical traditions of phenomenology and hermeneutics, the present study presents Danish general practitioners' (GPs') experiences and interpretations of why the existential and spiritual dimensions are marginalized in patient care. We conducted seven focus groups, constituting a total sample of 31 GPs. Based on the analytic strategy of Interpretative Phenomenological Analysis (IPA), our analysis revealed that the GPs experienced and interpreted individual barriers as created and fostered within dominant biomedical and secular cultures that are characterized as 'solution focused' and 'faith frightened'. Many GPs further understand themselves as barriers, because they are enculturated into these dominating cultures. We discuss these findings through theoretical concepts such as 'secondary socialization', 'system colonization' and 'secularization', and suggest interventions that might challenge current practice culture.